Spatial segregation in a sexually dimorphic central place forager: Competitive exclusion or niche divergence?. Issue 10 (29th June 2021) - Orgeret, Florian; Reisinger, Ryan R.; Carpenter‐Kling, Tegan; Keys, Danielle Z.; Corbeau, Alexandre; Bost, Charles‐André; Weimerskirch, Henri; Pistorius, Pierre A.
Abstract: Sexual competition is increasingly recognized as an important selective pressure driving species distributions. However, few studies have investigated the relative importance of interpopulation versus intrapopulation competition in relation to habitat availability and selection. To explain spatial segregation between sexes that often occurs in non‐territorial and central place foragers, such as seabirds, two hypotheses are commonly used. The 'competitive exclusion' hypothesis states that dominant individuals should exclude subordinate individuals through direct competition, whereas the 'niche divergence' hypothesis states that segregation occurs due to past competition and habitat specialization. We tested these hypotheses in two populations of an extreme wide‐ranging and sexually dimorphic seabird, investigating the relative role of intrapopulation and interpopulation competition in influencing sex‐specific distribution and habitat preferences. Using GPS loggers, we tracked 192 wandering albatrosses Diomedea exulans during four consecutive years (2016–2019), from two neighbouring populations in the Southern Ocean (Prince Edward and Crozet archipelagos). We simulated pseudo‐tracks to create a null spatial distribution and used Kernel Density Estimates (KDE) and Resource Selection Functions (RSF) to distinguish the relative importance of within‐ versus between‐population competition. Kernel Density Estimates showed that only intrapopulation sexual segregation was significant for each monitoring year, and that tracks between the two colonies resulted in greater overlap than expected from the null distribution, especially for the females. RSF confirmed these results and highlighted key at‐sea foraging areas, even if the estimated of at‐sea densities were extremely low. These differences in selected areas between sites and sexes were, however, associated with high interannual variability in habitat preferences, with no clear specific preferences per site and sex. Our results suggest that even with low at‐sea population densities, historic intrapopulation competition in wide‐ranging seabirds may have led to sexual dimorphism and niche specialization, favouring the 'niche divergence' hypothesis. In this study, we provide a protocol to study competition within as well as between populations of central place foragers. This is relevant for understanding their distribution patterns and population regulation, which could potentially improve management of threatened populations. Abstract : Sexual competition is increasingly recognized as an important selective pressure driving species distributions. In this study, the authors provide a new protocol to better investigate the causes of sexual segregation which is relevant for understanding population distribution patterns and population regulation, and could improve management of threatened species.